Virtual Leadership – Chances and Limitations - Michael WENZEL (Communications of International Proceedings, 2021)
The digitization of the private life and work environment is further continuing and growing into new aspects. The chance for digital communication and digital collaborative work was especially during the situation of the Corona pandemic an important solution for many companies to keep big parts, if not even all, of their daily business processes active by enabling their employees to work from their home offices. Currently these changes are being part of discourse in public media and press, if the struggle for more home office work for more people shall remain also after the Corona pandemic situation or not. This public discourse is often driven from the side and perspective of the employees and brought into context with work-life-balance advantages. Beside legal requirements of home offices for employees and cost aspects for the employers, also the question needs to be addressed, how working in virtual teams might affect processes within the companies. What influence does the remote work with virtual teams for example have on the change processes or even multi-layer change processes many companies go through right now and in future? What extra challenges will it bring to the management of organizations, or might it even ease and support change processes by an inherent change of mindsets what a virtual work environment can bring?
Keywords: Virtual Leadership; Change Management; Chances; Limitations